The Willingness of Jordanian EFL Teachers to Endure Taking Online Professional Development Programs Rather Than Face to Face - Slim, Suha Abdulrazzaq (Journal of Educational and Psychological Sciences, 2020)
This study attempts to investigate the willingness of Jordanian EFL teachers to endure taking Online Professional Development Programs (OPD) rather than face to face learning in both private and public schools. Therefore, a qualitative research methodology was carried out to examine the extent to which Jordanian EFL teachers are willing to endure taking Online Professional Development Programs (OPD) rather than face to face learning. Data were collected via online interviews with teachers through e-Learning forums as well as other means of interactive social Medias such as Zoom, Facetime and Microsoft teams during COVID-19 Pandemic in the second semester of the scholastic year 2019-2020. Ten EFL teachers were randomly chosen from forty public and private EFL school teachers to respond to the interviews. The sample consisted of ten teachers who were selected randomly for the interview. The interview content focused on two domains which are: the challenges faced teachers in online learning and the good learning practices experienced by EFL teachers during online learning regarding their experiences through the pandemic. The interviews were taking the form of semi-structured interviews. The findings of the study revealed that the majority of EFL teachers are unwilling to continue taking online professional development programs as they faced many troubles and obstacles through experiencing distant learning during the COVID-19 Pandemic as part of their first hands on experience. Two teachers showed a tendency to continue Online Professional Development Programs in parallel with face to face programs.